Histopathologic Characteristics of a Chronic Arteriovenous Malformation in a Swine Model: Preliminary Study - Massoud, Tarik F.; Vinters, Harry V.; Chao, Kuo H.; Viñuela, Fernando; Jahan, Reza (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: The experimental induction of histologic transformations in microvessels of similar caliber to those of nidus vessels of cerebral arteriovenous malformations (AVMs) has not been attempted previously. Our goal was to examine preliminarily the histopathologic characteristics of nidus vessels and the angiographic features of a chronic AVM model in swine.METHODS: AVM models were fashioned from bilateral carotid retia mirabilia of seven swine after the surgical formation of large unilateral carotid-jugular fistulas. One AVM model was made for immediate use, whereas in the other six, follow-up angiography was obtained at varying intervals (2 to 180 days) after model creation. Light and electron microscopy, immunohistochemistry (using monoclonal antibodies against smooth muscle actin and PC10 against proliferating cell nuclear antigen), and histometry were performed on the nidus vessels of three swine: one acutely created, one 2 months old, and one 6 months old.RESULTS: Vascular dilatation and tortuosity of the main arterial feeder and draining vein were evident angiographically as early as 4 days after AVM creation, and were maximal in the 6-month-old model. Compared with the acutely created nidus vessels, those in the two chronic models revealed disrupted and attenuated elastica and intimal hyperplasia that was focal (“cushions”) or generalized, leading to luminal occlusion. Variable numbers of cells in the tunica media of chronic nidus vessels contained smooth muscle actin. PC10/proliferating cell nuclear antigen immunoreactivity was observed in the endothelium and subendothelial layers. Histometry showed increases in intimal hyperplasia and medial thickness in the chronic vessels.CONCLUSION: Nidus vessels in this chronic swine AVM model exhibited striking histologic changes similar to those seen in cerebral AVMs. The induced vessel growth seen angiographically and histologically in components of the chronic AVMs was consistent with the presence of persistently raised intravascular hemodynamic loads. This preliminary feasibility study suggests that the realistic histologic characteristics of this chronic AVM model are an attractive feature, and if confirmed in future, more comprehensive, studies would be of benefit in accurate histopathologic interpretation of the effects of superimposed experimental embolotherapy or radiosurgery. This model may provide a useful experimental tool to study the dynamic cellular and tissue events that dictate the development and natural history of AVMs.